Analisis Perubahan Garis Pantai Berdasarkan Data Citra Satelit di Wilayah Pesisir Kota Makassar Provinsi Sulawesi Selatan - Usman Usman; Muhammad Azis Irbani (Universitas Negeri Makassar, 2019)
This study aims to analyze the changes in the coastline in the coastal of Makassar city by using Digital Shoreline Analysis System (DSAS) method. The data used in this study was secondary data in the form of Landsat 5 and Landsat 8 digital satellite data which were acquired on 8 April 2019 and have been corrected radiometrically and geometrically obtained from the Lembaga Penerbangan dan Antariksa Nasional (LAPAN). The data was processed using ArcGIS 10.3 to obtain the overlay result. Shoreline Movement (NSM) and End Point Rate (EPR) methods used to calculate shoreline change calculations. Observation of shoreline changes takes 12 years using data in 2006, 2010, 2013, and 2018. Based on the results of the analysis with the method of Digital Shoreline Analysis System (DSAS) found that during 12 years the coast of Makassar experienced a change in coastline which is accretion due to reclamation that occurred in Tallo and Tamalate sub-districts.